2015
DOI: 10.3389/fpsyg.2015.00563
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting motivational orientation and evaluative coding accounts: on the need to differentiate the effectors of approach/avoidance responses

Abstract: Several emotion theorists suggest that valenced stimuli automatically trigger motivational orientations and thereby facilitate corresponding behavior. Positive stimuli were thought to activate approach motivational circuits which in turn primed approach-related behavioral tendencies whereas negative stimuli were supposed to activate avoidance motivational circuits so that avoidance-related behavioral tendencies were primed (motivational orientation account). However, recent research suggests that typically obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 61 publications
1
34
2
Order By: Relevance
“…In a recent review paper on theoretical explanations of affective stimulus-response compatibility (aSRC) effects between positive/negative stimuli and approach/avoidance-related movements, Kozlik et al ( 2015 ; KNL) argue that an evaluative-coding approach cannot fully account for aSRC effects with facial actions and that motivational orientations provide a better explanation. Their arguments are based on three observations that they consider incompatible with an evaluative-coding approach (Eder and Rothermund, 2008 , ER) and the Theory of Event Coding (TEC; Hommel et al, 2001 ) from which the approach is derived: (1) attempts to dissociate evaluative coding and motivational orientation showed separable contributions from these two factors (Krieglmeyer et al, 2010 ); (2) aSRC can be easily changed in manual actions (by instructions of action labels) but hardly in facial actions (Neumann et al, 2014 ); and (3) the hemispheric asymmetry in the control of positive/negative facial expressions matches the hemispheric asymmetry assumed for motivational orientations (Davidson et al, 1990 ).…”
mentioning
confidence: 99%
“…In a recent review paper on theoretical explanations of affective stimulus-response compatibility (aSRC) effects between positive/negative stimuli and approach/avoidance-related movements, Kozlik et al ( 2015 ; KNL) argue that an evaluative-coding approach cannot fully account for aSRC effects with facial actions and that motivational orientations provide a better explanation. Their arguments are based on three observations that they consider incompatible with an evaluative-coding approach (Eder and Rothermund, 2008 , ER) and the Theory of Event Coding (TEC; Hommel et al, 2001 ) from which the approach is derived: (1) attempts to dissociate evaluative coding and motivational orientation showed separable contributions from these two factors (Krieglmeyer et al, 2010 ); (2) aSRC can be easily changed in manual actions (by instructions of action labels) but hardly in facial actions (Neumann et al, 2014 ); and (3) the hemispheric asymmetry in the control of positive/negative facial expressions matches the hemispheric asymmetry assumed for motivational orientations (Davidson et al, 1990 ).…”
mentioning
confidence: 99%
“…By associating valence and action information to either cue or target features in different blocks within the same task, the present paradigm allowed to test additional predictions with regard to different control processes and their contribution to valence-action biases (research question 2). This is inspired by the observation that the majority of studies in the motivational domain use cuing procedures, that are known to trigger preparatory control mechanisms (Braver et al, 2014;Krebs & Woldorff, 2017), while studies on emotional valence-action biases mostly feature valence targets, thereby probing more immediate (and potentially even automatic) effects (Bargh et al, 1996;Chen & Bargh, 1999;Kozlik et al, 2015). We hypothesized that valence-action biases would be pronounced in trials in which valence and action signals are directly associated with targets as compared to cues, considering that there is less room for controlled, preparatory mechanisms (Chiew & Braver, 2016), and in turn a higher probability of (automatic) response activation (Krebs & Woldorff, 2017;Ridderinkhof, Forstmann, Wylie, Burle, & van den Wildenberg, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Reaching towards a tasteful cookie and backing off from a spider is evidently easier than performing the opposite actions when facing these stimuli. This phenomenon, which has been described as valence-action bias (Elliot, 2006;Phaf, Mohr, Rotteveel, & Wicherts, 2014;Solarz, 1960), is thought to arise from a fairly automatic evaluation of a given stimulus, which in turn triggers inherent approach and avoidance tendencies (Bargh, Chaiken, Raymond, & Hymes, 1996;Chen & Bargh, 1999;Kozlik, Neumann, & Lozo, 2015). However, there is also work suggesting a more indirect link between valence and action relying on more conscious appraisal (Phaf et al, 2014;Rotteveel & Phaf, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A prevalent discussion in the literature on the automatic activation of approach–avoidance tendencies centers around the question whether affective stimuli trigger specific motor patterns of approach–avoidance (e.g., arm flexion and extension) or a rather flexible mechanism of distance regulation ( Krieglmeyer et al, 2013 ; Kozlik et al, 2015 ). In particular, early studies demonstrated a link between positive valence and arm flexion, and negative valence and arm extension ( Cacioppo et al, 1993 ; Chen and Bargh, 1999 ; Rotteveel and Phaf, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regulating behavior toward positive and away from negative stimuli is a vital function of living organisms. To fulfill this regulatory need, evaluation of stimulus valence automatically results in the activation of approach and avoidance tendencies (for reviews and meta-analyses, see Phaf et al, 2014 ; Kozlik et al, 2015 ; Laham et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%